A comprehensive comparison between GaN MMIC Doherty and combined class-AB power amplifiers for microwave radio links. Issue 4 (11th February 2016) - Giofrè, Rocco; Colantonio, Paolo; Giannini, Franco; Ramella, Chiara; Camarchia, Vittorio; Iqbal, Mustazar; Pirola, Marco; Quaglia, Roberto
Abstract : A combined class-AB and a Doherty power amplifier conceived for microwave backhaul in the 7 GHz frequency band are here presented and compared. They are fabricated in the same GaN monolithic process and have identical total active device periphery. For the given application, the linearity-efficiency trade-off for the two architectures is discussed. The two modules have been thoroughly characterized in linear and non-linear continuous wave conditions. Then, to evaluate linearity under the actual operative conditions, a system level characterization has been carried out, applying a modulated input signal and comparing the spectral responses of the two amplifiers with and without digital predistortion. A saturated output power of 40 dBm has been achieved by both circuits. At 6 dB of output back-off, the Doherty amplifier shows an efficiency of 33%, 10 points higher than that of the class-AB module. On the other hand, system level measurements show that, adopting the same predistorter complexity to comply with the reference standard emission masks, the Doherty amplifier needs at least 1 dB of extra back-off. This negatively affects its efficiency, therefore reducing the advantages it can claim with respect to the class-AB amplifier in continuous wave condition.